Reality check: testing the in silico predictions of false negative results due to mutations in SARS-CoV-2 PCR assays using templates with mismatches in vitro - Otwell, Taylor; Knight, Brittany; Coryell, Michael; Stone, Jennifer; Davis, Phillip; Necciai, Bryan; Carlson, Paul; Sozhamannan, Shanmuga (Frontiers in Cellular and Infection Microbiology, 2025)
Molecular diagnostic assays are critical tools to test, diagnose and treat infectious and other diseases. For example, PCR test results have been extremely valuable during the COVID-19 pandemic, not only to provide appropriate health care for infected and symptomatic individuals as needed, but also for implementing public health measures such as test, trace and isolate infected and asymptomatic individuals to prevent further transmission of the virus. Sustained transmission and unhindered proliferation of the pathogen across the population during a continuous, ongoing pandemic such as COVID-19, resulted in many variants with mutations. These mutations may lead to signature erosion, a phenomenon wherein diagnostic tests developed using the genomic sequence of an earlier version of the pathogen, may fail and cause a false negative (FN) result in a sample containing a new variant. We and others have developed applications such as PSET (PCR Signature Erosion Tool) to monitor the performance of diagnostic tests in silico using pathogen genomic sequences. Here, we present and discuss the data on wet lab testing of the in silico predictions to assess assay performance with mismatches in assay signatures. We found that the majority of the assays performed without drastic reduction in assay performance even with mismatches in primer and probe regions as measured by PCR efficiencies and Ct value shifts. We identified critical residues and positions and types of changes that may impact assay performance. Despite the extensive accumulation of mutations in SARS-CoV-2 variants over the course of the various waves of the pandemic, most PCR assays proved to be extremely robust and continued to perform well even with drastic changes and signature erosion.